Using Archetypes to Design Services for High Users of Healthcare - Samuel Vaillancourt, Ilan Shahin, Payal Aggarwal, Steve Pomedli, Leigh Hayden, Laura Pus and Onil Bhattacharyya (HealthcarePapers, 2014)
A subset of people with complex health and social needs account for the majority of healthcare costs in Ontario. There is broad agreement that better solutions for these patients could lead to better health outcomes and lower costs, but we have few tools to design services around their diverse needs. Predictive modelling may help determine numbers of high users, but design methods such as user archetypes may offer important ways of understanding how to meet their needs. We studied a range of patient profiles and interviews with frequent emergency department users to develop four archetypes of patients with complex needs to orient the service design process. These can be refined and adapted for use within initiatives like Health Links to help provide more appropriate cost-effective care.
Keywords: high users of healthcare, health system sustainability, integration, appropriateness of care, government spending, health expenditures